Low temperature synthesis and spark plasma sintering of a boron carbide with a low residual carbon content. Issue 2 (February 2022) - Kenny, Jonathan; McDonald, Nikkia; Binner, Jon; Hong Chang, Isaac Tsz; Marinel, Sylvain
Abstract: Using spark plasma sintering (SPS), >98.5 % dense boron carbide (B4 C) samples were made from commercially available and lab-synthesised powders made via a low temperature synthesis (LTS) process. The work showed that the LTS powder can be produced in batches of tens to hundreds of grams whilst maintaining a high purity material with lower levels of residual free carbon (20.6–21.3 wt.% C) than commercially available samples (22.4 wt.% C). The LTS material was seen to exhibit higher hardness values (37.8 GPa) than the commercial grade material (32.5 GPa) despite featuring a coarser average grain size (10.8 μm and 2.4 μm respectively). This is largely thought to be due to the influence of ZrO2 and AlB2 impurities introduced to the material during micronising milling of the powder after synthesis, as opposed to the influence of the materials lower carbon content.